Partnership for Empowering Community Learning Centers in Improving Competency in Managing Vocational Skills Training - Tri Suminar; Tri Joko Raharjo; Bagus Kisworo; Yudi Siswanto; Lintang Markhamah Watianur Azizah; Ella Elistiani; Itsnaini Iflachatun Azkiya; Ganeza Adien Marcella (Universitas Negeri Semarang, 2023)
Abstract. The partner of this community service activity is Bina Sejahtera Community Learning Center of Brebes Regency, which faces problems in managing vocational skills training programs for Package C equivalency education students, less effectively. The specific objective of empowering the Community Learning Center managers is that they can manage a systematic vocational training program, which has an impact on increasing the interest in learning of students in Package C until graduation and are able to develop vocational skills in a sustainable manner. This empowerment partnership is implemented with a participatory approach that places the target as a facilitator, motivator and dynamizer in FGDs, workshops and practical activities. The results of this community service partnership show that the manager of the Community Learning Center can implement competency-based training program management starting from training planning based on the results of organizational, job / position and individual needs analysis. Vocational training programs are formulated based on digital entrepreneurship (digital printing). Training implementation is monitored to measure the suitability of training implementation with planning and evaluated to measure the achievement of training program objectives. The results of the training program evaluation are followed up by developing a follow-up plan for the training program, namely establishing cooperation with stakeholders. The impact of digital printing press mug entrepreneurship training practices for learners is an increased interest in learning at Pack C equivalency. Learning in vocational training is important to encourage the completion of 12-year compulsory education for adults who are not in school and have a positive attitude towards digital entrepreneurship.